Adsorption of reactive orange 13 onto jackfruit seed flakes in aqueous solution. Issue 1 (March 2015) - Karmaker, Subarna; Uddin, Md. Naim; Ichikawa, Hideki; Fukumori, Yoshinobu; Saha, Tapan Kumar
Highlights Adsorption of RO13 onto jackfruit seed flakes was investigated in aqueous solution. Adsorption kinetics follows pseudo second-order model. Intraparticle diffusion and film diffusion are the rate limiting steps. Equilibrium adsorption behaviors follows Langmuir isotherm model. The present adsorption is spontaneous and endothermic physisorption process.